Efficacy of β-Blockers on Postural Tachycardia Syndrome in Children and Adolescents: A Systematic Review and Meta-Analysis - Deng, Xinwei; Zhang, Yuyang; Liao, Ying; Du, Junbao (Frontiers in Pediatrics, 2019)
Abstract Background: Postural tachycardia syndrome (POTS) is a severe health problem in children. Short-term β-blockers are recommended for pharmaceutical treatment. However, there have been contradictory data about its efficacy among pediatric patients. Methods and Results: Eight studies comparing β-blockers to conventional treatments for children with POTS were selected, where 497 cases of pediatric POTS were included. The efficacy of β-blockers was evaluated using the effective rate, the change of symptom score, the change of heart rate difference and adverse events. The results were stated as relative ratio (RR) and mean difference (MD) with a 95% confidence interval (95% CI). A random effects meta-analysis for the effective rate indicated that β-blockers were more effective in treating pediatric POTS than controlled treatment (79.5% versus 57.3%, RR=1.50, 95%CI: 1.15-1.96, P<0.05). A fixed-eﬀects model analysis showed that β-blockers were more effective in lowering the symptom score and the heart rate increment during standing test than controlled treatment with a mean difference of 0.81 (95% CI: 0.44-1.18, P<0.05) and 3.78 (95% CI: 2.10-5.46, P<0.05), respectively. There were no reported severe adverse events in included studies. Conclusion: β-blockers are effective in treating POTS in children and adolescents, alleviating orthostatic intolerance, and improving hemodynamic abnormalities.